When you have something like this, all you need to do is substitute the values, the last is for what value of x
For the first one;
((x^2+1)+(x-2))(2)
(x^2+x-1)(2)
(2)^2+(2)-1
4+2-1
5
For the second one;
((x^2+1)-(x-2))(3)
(x^2-x+3)(3)
(3)^2-(3)+3
9-3+3
9
For the last one;
3(x^2+1)(7)+2(x-2)(3)
3((7)^2+7)+2((3)-2)
3(49+7)+2(3-2)
3(56)+2(1)
168+2
170
I would say the cube because it takes more space (volume) than the row of cubes
"Not sure if it makes sense but, eh...."
Answer:
The constant of proportionality gives you the price per unit at each store.
Step-by-step explanation:
If you assume that the price (y) is directly proportional to the amount (x) you get, the formula is
y = kx
where k is the constant of proportionality.
k = y/x
k has the units of cost per unit, for example, dollars per ounce.
The fewer the dollars per ounce, the better the deal you are getting.
If store A offers apple sauce at $1.29 for 25 oz and Store B offers apple sauce at $2.89 for 50 oz, which is the better deal?
At store A, k = $1.29/25 oz = $0.052/oz or 5.2¢/oz
At store B, k = $2.89/50 oz = $0.058/oz or 5.8¢/oz
The apple sauce is cheaper at Store A.
Answer:
(2/3)x = -11
x = -33/2
Step-by-step explanation:
2/3 of a number is -11.
Let the unknown number be x.
2/3 of x is -11.
(2/3)x = -11
Multiply both sides by 3/2.
(3/2)(2/3)x = (3/2)(-11/1)
x = -33/2